Pregnancy and melanoma: a European‐wide survey to assess current management and a critical literature overview. (27th May 2016) - Ribero, S.; Longo, C.; Dika, E.; Fortes, C.; Pasquali, S.; Nagore, E.; Glass, D.; Robert, C.; Eggermont, A.M.; Testori, A.; Quaglino, P.; Nathan, P.; et al.
Abstract: Background: Management of melanoma during pregnancy can be extremely challenging. The reported incidence of melanoma in pregnancy ranges from 2.8 to 5.0 per 100 000 pregnancies. There are no guidelines for the management of melanoma during pregnancy. Methods: The survey was designed to investigate the opinions of melanoma physicians on decision making in relation to pregnancy and melanoma. A clinical scenario‐based survey on management of pregnancy in melanoma was distributed all over Europe via the membership of the EORTC and other European melanoma societies. Results: A total of 290 questionnaires were returned with a larger participation from southern Europe. A large heterogeneity was found for the answers given in the different clinical scenarios with 50% of the answers showing discordance, especially regarding sentinel lymph node biopsy during pregnancy. Discordant answers were also found for the counselling of women about a potential delay in getting pregnant after a high‐risk melanoma (35% for a 2 year wait minimum vs. 57% no waiting needed), while for thin melanomas, as expected, there was more concordance with 70% of the physicians recommending no delay. Fifteen per cent of physicians recommended an abortion in stage II melanoma during the third month of pregnancy. Twenty per cent of the responders advised against hormonal replacement therapy in melanoma patients. Conclusions: The management of melanoma during pregnancy varies widely in Europe. At present, there is a lack of consensus in Europe, which may lead to very important decisions in women with melanoma, and guidelines are needed.